Emotional interference and attentional processing in premenstrual syndrome. (March 2017) - Eggert, Lisa; Kleinstäuber, Maria; Hiller, Wolfgang; Witthöft, Michael
Abstract: Background and objectives: Premenstrual syndrome (PMS) is characterized by menstrual cycle-related affective, behavioral, and/or somatic symptoms. By applying the emotional Stroop task (EST) the current study examined if changes in processing emotional information, which have been demonstrated in affective disorders, are also present in PMS. Methods: Via online screening, telephone interviews, and daily records over two months 55 women for the PMS group (on the basis of the specific inclusion criteria and a prospectively confirmed PMS) and 55 'non-PMS' controls were recruited. All participants completed three emotional Stroop tasks (EST) with neutral and negative word, picture, and facial stimuli, during the follicular and luteal phase of the menstrual cycle. Results: Mixed 2 × 2 univariate analyses of variance and post-hoc comparisons showed primarily a greater emotional Stroop effect with respect to picture and facial stimuli in the luteal menstrual cycle phase in women with PMS, compared to the control group. No significant group differences were observed for word stimuli. With respect to the facial stimuli, a kind of paradox effect was revealed (Stroop facilitation) in the PMS group. Limitations: This study provides important information regarding cognitive processes in women suffering from PMS that have to be interpreted in the light of the following limitations: a limited representativeness of the sample, the determination of menstrual cycle phases based on symptom diaries but not hormone levels, and a limited interpretability of our results as causal relationships. Conclusions: Our findings are in line with the assumption that alterations in cognitive-emotional processes are associated with PMS. Further research on the etiology of PMS should focus more on cognitive-emotional processing and its interaction with biological changes relating to the menstrual cycle. Highlights: We examined if women with PMS show alterations in processing emotional information. Emotional Stroop (ES) test was applied to examine implicit emotion regulation. Implicit emotion regulation differed between women with and without PMS. An altered ES effect in the luteal menstrual cycle phase was shown in the PMS group.